2015
DOI: 10.1007/s12011-015-0410-8
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Induced Effects of Molybdenum and Cadmium on the Trace Elements and the mRNA Expression Levels of CP and MT in Duck Testicles

Abstract: To investigate the chronic toxicity of molybdenum (Mo) and cadmium (Cd) on the trace elements and the mRNA expression levels of ceruloplasmin (CP) and metallothionein (MT) in duck testicles, 120 healthy 11-day-old male ducks were randomly divided into six groups with 20 ducks in each group. Ducks were treated with the diet containing different dosages of Mo or Cd. The source of Mo and Cd was hexaammonium molybdate ([(NH4)6Mo7O24·4H2O]) and cadmium sulfate (3CdSO4·8H2O), respectively, in this study. After being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Zn is an essential trace element, and is the component of more than 300 enzymes related to cell metabolism and gene expression. Cd can replace Zn and bind to MT, resulting in the redistribution of Zn in the cytoplasm and serum (Xia et al 2016). Previous studies have reported that 1-day-old broiler chickens exposed to 100 mg/kg Cd had higher concentrations of Cu and lower concentrations of Mn and Fe in the kidney (Al-Waeli et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Zn is an essential trace element, and is the component of more than 300 enzymes related to cell metabolism and gene expression. Cd can replace Zn and bind to MT, resulting in the redistribution of Zn in the cytoplasm and serum (Xia et al 2016). Previous studies have reported that 1-day-old broiler chickens exposed to 100 mg/kg Cd had higher concentrations of Cu and lower concentrations of Mn and Fe in the kidney (Al-Waeli et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The fertility-related protein markers ENO1, ATP5B, VDAC2, GPX4, and UQCRC2 were identi ed from 20 individual bull semen samples [38]. CP is a Cu-containing protein and an oxidase with high antioxidation capacity, which is involved in scavenging oxygen free radicals and protecting various organs from lipid peroxidation and other types of oxidative attack in the extracellular space [39]. Dietary addition of Mo indirectly increases oxidative stress to exacerbate Cd toxicity by reducing the expression of MT and CP, which protect testicles from lipoperoxidation and other types of oxidative stress [40].…”
Section: Discussionmentioning
confidence: 99%